2018
DOI: 10.1002/jbm.a.36593
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of chitosan and BMP‐2 tuned by deacetylation degree and pH value

Abstract: Integrating proteins with chitosan (CS) can not only improve the biocompatibility of CS, but also enable the sustained release of proteins. The deacetylation degree (DD) and pH conditions are considered as the two most important factors affecting the interaction between CS and proteins. In this study, the effects of CS with different DDs and pH conditions on bone morphogenetic protein‐2 (BMP‐2) adsorption were evaluated using the molecular dynamics (MD) method. The results showed that the interaction energy fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
(70 reference statements)
1
13
0
Order By: Relevance
“…Although both BMP‐2 and CS are positively charged, molecular dynamics simulations by Wang et al showed an attractive interaction of these two substances, which depends on the degree of deacetylation of CS (Wang et al, 2019). Experimentally, a loading of CS particles with BMP‐2 could only be shown for sulfated CS so far (Cao, Wang, Hou, Xing, & Liu, 2014), which is to be expected because of the known interaction of BMP‐2 with sulfated glycosaminoglycans such as heparin.…”
Section: Discussionmentioning
confidence: 99%
“…Although both BMP‐2 and CS are positively charged, molecular dynamics simulations by Wang et al showed an attractive interaction of these two substances, which depends on the degree of deacetylation of CS (Wang et al, 2019). Experimentally, a loading of CS particles with BMP‐2 could only be shown for sulfated CS so far (Cao, Wang, Hou, Xing, & Liu, 2014), which is to be expected because of the known interaction of BMP‐2 with sulfated glycosaminoglycans such as heparin.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan is known to bind BMP-2 although both molecules have an overall positive charge at neutral pH [27]. The chitosan binding may have a solubilizing effect on BMP-2 by preventing its ionic self-interaction (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…Left (without chitosan): Ionic BMP-2 self-interaction, leading to BMP-2 aggregation [23]. Right: Binding of chitosan to the negatively charged tips of BMP-2 [27], potentially leading to a decreased aggregation tendency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan, a biopolymer derived from chitin, has many useful properties such as biocompatibility, biodegradability, and antimicrobial properties, and has been extensively studied for applications in tissue engineering (Wang et al, 2019). PVA is a water-soluble, biodegradable and non-toxic polymer.…”
Section: Discussionmentioning
confidence: 99%